2012
DOI: 10.1093/mutage/ges036
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment and detoxification induction in Dreissena polymorpha exposed to benzo[a]pyrene

Abstract: The use of DNA adduct analysis has previously focused on the use of marine organisms for biomonitoring, whereas similar investigations in freshwater organisms are sparse. In that context, we have investigated the relevance of DNA adducts as biomarkers of genotoxicity in the freshwater mussels Dreissena polymorpha. The objective of the present study is to determine the stability of DNA adducts induced by benzo[a]pyrene (B[a]P) in zebra mussels. Mussels were exposed to dissolved B[a]P (10-100 µg/l) for 4 days. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…In the same way, Rocher et al (2006) also observed DNA adduct amounts in zebra mussels collected in stations from the Seine estuary and the Seine Bay around 10 adducts/10 9 nt. The same range of DNA adduct formation was previously noticed in laboratory experiments where D. polymorpha exposed to Benzo[a] pyrene depicted DNA adducts ranging from 1.3 to 5.19 adducts/10 9 nucleotides in gills and from 0.9 to 2.29 adducts/10 9 nucleotides in the digestive glands (Châtel et al, 2012). This was also comparable to marine mussels exposed to the same xenobiotic (Canova et al, 1998;Skarphéinsdóttir et al, 2003;Akcha et al, 2000).…”
Section: Dna Adduct Formationsupporting
confidence: 83%
See 3 more Smart Citations
“…In the same way, Rocher et al (2006) also observed DNA adduct amounts in zebra mussels collected in stations from the Seine estuary and the Seine Bay around 10 adducts/10 9 nt. The same range of DNA adduct formation was previously noticed in laboratory experiments where D. polymorpha exposed to Benzo[a] pyrene depicted DNA adducts ranging from 1.3 to 5.19 adducts/10 9 nucleotides in gills and from 0.9 to 2.29 adducts/10 9 nucleotides in the digestive glands (Châtel et al, 2012). This was also comparable to marine mussels exposed to the same xenobiotic (Canova et al, 1998;Skarphéinsdóttir et al, 2003;Akcha et al, 2000).…”
Section: Dna Adduct Formationsupporting
confidence: 83%
“…S3 ribosomal gene was chosen as the reference gene for normalization as previously demonstrated (Contardo-Jara et al, 2010;Châtel et al, 2012). Table 1 Primer sequences (5 0 -3 0 ) used in qRT-PCR.…”
Section: Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though bivalve BaP metabolisation remain lower than in vertebrates, zebra mussel gill cells are able to transform the BaP into active metabolite which can induce DNA lesions such as bulky DNA adducts as we recently observed in gills and digestive gland (Chatel et al 2012). BaP induced DNA SB has been largely observed in bivalve species such as for example Mytilus sp.…”
Section: Generation Of Dna Lesions By Bap and Repairmentioning
confidence: 87%